Evaluation of Congo red dye decolorization and degradation potential of an endophyte Colletotrichum gloeosporioides isolated from Thevetia peruviana (Pers.) K. Schum - Bharti, Rajnish; Yadav, Monika; Singh, Arti; Kumari, Puja; Nishad, Jay Hind; Gautam, Veer Singh; Kharwar, Ravindra Nath (Folia microbiologica, 2023)
Decolorization and degradation of textile dye by endophytic fungi stand to be a profitable and viable alternative over conventional methods with respect to eco-friendliness, cost-effectiveness, and non-hazardous nature. One of the active fungal endophytes Colletotrichum gloeosporioides isolated from plant Thevetia peruviana (Pers.) K. Schum. was screened for laccase production and Congo red dye decolorization. Various physicochemical parameters like dye concentration, carbon sources, nitrogen sources, temperature, and pH were optimized, and the maximum decolorization (%) was achieved at 100 mg/L of dye concentration (82%), yeast extract (80%), 30 °C temp (80%), glucose (79%), and 7 pH (78%), respectively. SEM image and fungal biomass changes represent that fungus actively participated in the dye decolorization and had less significant effect on biomass. The regenerative ability of fungus C. gloeosporioides after dye decolorization indicated tolerance against the dye and was found to be more advantageous over previous reports of dye decolorization by other endophytic fungi. UV-Vis spectra, TLC, FTIR, and HPLC results confirmed the decolorization and degradation process due to absorption and biodegradation. Phytotoxicity assay depicted that degraded products are less toxic to Phaseolus mungo compared to Congo red. The overall findings showed that C. gloeosporioides possesses a good decolorization and degradation potential against Congo red and this endophyte can be profitably used for dye-containing wastewater treatment.
Keywords: Kongo červeň; Colletotrichum; Congo Red; Endophytes; Coloring Agents; Thevetia; endofyty; Biodegradation, Environmental; biodegradace; barvicí látky